Screened potential and quarkonia properties at high temperatures - Vijande, J.; Krein, Gastão Inácio [UNESP]; Valcarce, A. (Springer, 2009)
We perform a quark model calculation of the quarkonia b (b) over bar and c (c) over bar spectra using smooth and sudden string breaking potentials. The screening parameter is scale dependent and can be related to an effective running gluon mass that has a finite infrared fixed point. A temperature dependence for the screening mass is motivated by lattice QCD simulations at finite temperature. Qualitatively different results are obtained for quarkonia properties close to a critical value of the deconfining temperature when a smooth or a sudden string breaking potential is used. In particular, with a sudden string breaking potential quarkonia radii remain almost independent of the temperature up to the critical point, only well above the critical point the radii increase significantly. Such a behavior will impact the phenomenology of quarkonia interactions in medium, in particular for scattering dissociation processes.